Editorial - Pasierbek, Wit (Horyzonty Wychowania, 2017)
The concept of ethos, taking into account the frequency of its usage, for instance in the debates of thinkers, politicians and media people, appears settled in our culture, language and consciousness. On the other hand, everyday day that we experience repeatedly seems to challenge this postulated omnipresence and significance of ethos. What does it prove?